IMPLEMENTASI PROGRAM PENGEMBANGAN KELEMBAGAAN DI SMART FISHERY VILLAGE (SFV) PENGAMBENGAN, KABUPATEN JEMBRANA, PROVINSI BALI - Annisa Khairani Aras; Ilham; Mohsan Abrori; I Nyoman Sudiarsa; Liga Insani; Arie Kiswanto; Diah Ayu Satyari Utami; Anik Kusmiatun; Andina Chairun Nisa; Diklawati Jatayu; Amiqatul Fikriyah; Muhammad Chaidir Undu (LP2M Universitas Hasanuddin, 2024)
This community service activity in the aquaculture community at SMART Fishery Village (SFV) Pengambengan aims to increase understanding and management skills of institutional administration and the formation of the SFV Pengambengan secretariat. The problems faced by partners are the lack of insight and knowledge of the group in advancing the business, the implementation of institutional administration that is less than optimal and not yet neatly arranged, and the absence of a permanent SFV Pengambengan secretariat. The method for implementing this service is to provide technical guidance regarding institutional administration management through the preparation of simple financial reports and partner participation by providing improvements to the SFV Pengambengan secretariat facilities that are more appropriate. The result of this community service activity is that partners experience increased understanding and skills in managing institutional administration in the form of preparing simple financial reports. Partners understand the types of costs, identify financial transactions in vaname shrimp cultivation activities, can keep financial journals, and can make simple financial reports per production cycle. The Pengambengan SFV secretariat can be formed permanently, making it easier for all members to gather, monitor, and assist ongoing production activities. || Kegiatan pengabdian kepada masyarakat pada Pokdakan di SMART Fishery Village (SFV) Pengambengan ini bertujuan adalah untuk peningkatan pemahaman dan keterampilan pengelolaan administrasi kelembagaan dan pembentukan sekretariat SFV Pengambengan. Masalah yang dihadapi mitra adalah minimnya wawasan dan pengetahuan kelompok dalam memajukan usaha, pelaksanaan administrasi kelembagaan yang kurang optimal dan belum tertata rapi serta belum adanya sekretariat SFV Pengambengan yang permanen. Adapun metode pelaksanaan pengabdian ini yakni bimbingan teknis tentang pengelolaan administrasi kelembagaan melalui pembuatan laporan keuangan sederhana dan partisipasi mitra dengan menyediakan perbaikan fasilitas sekretariat SFV Pengambengan yang lebih layak. Hasil dari kegiatan pengabdian masyarakat ini berupa mitra mengalami peningkatan pemahaman dan keterampilan dalam pengelolaan administrasi kelembagaan berupa pembuatan laporan keuangan sederhana. Mitra memahami jenis biaya, mengidentifikasi transaksi keuangan di kegiatan budidaya udang vaname, mampu membuat jurnal keuangan serta mampu membuat laporan keuangan sederhana per siklus produksi. Sekretariat SFV Pengambengan dapat terbentuk secara permanen dan memudahkan seluruh anggota untuk berkumpul, memonitoring dan pendampingan kegiatan produksi yang berlangsung.